1985
DOI: 10.1007/bf02620926
|View full text |Cite
|
Sign up to set email alerts
|

Selection of transfored cells in serum-free media

Abstract: NIH3T3 cells grow in a serum-free basal nutrient medium supplemented with fibronectin, transferrin, insulin, epidermal growth factor (EGF) and high density lipoprotein (HDL). The individual omission from the serum-free medium of insulin, EGF, or HDL results in greatly reduced cell growth. These growth-restrictive conditions can be used to select for cells transformed with SV40, the polyomavirus middle T antigen gene, the activated human ras gene, and the mouse c-myc gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that either EGF or aTGF alone is ineffective in promoting the soft agar growth of primary cultures of normal mouse or rat mammary epithelial cells, although both growth factors are mitogenic for these cells in monolayer culture (Zwiebel et al, 1982). Since the NMuMG cell line utilized in the present study represents a spontaneously immortalized population of mouse mammary epithelial cells, it is certainly possible that immortalization has further sensitized these cells to EGF or aTGF so as to permit their growth in soft agar in response to these growth factors (Kaplan and Ozanne, 1983;Marshall, 1984;Chiang et al, 1985). This may be the case since rat embryo fibroblasts that have been experimentally immortalized by transfection with a c-myc-containing plasmid acquire the ability to grow in soft agar in response to only EGF (Stern et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that either EGF or aTGF alone is ineffective in promoting the soft agar growth of primary cultures of normal mouse or rat mammary epithelial cells, although both growth factors are mitogenic for these cells in monolayer culture (Zwiebel et al, 1982). Since the NMuMG cell line utilized in the present study represents a spontaneously immortalized population of mouse mammary epithelial cells, it is certainly possible that immortalization has further sensitized these cells to EGF or aTGF so as to permit their growth in soft agar in response to these growth factors (Kaplan and Ozanne, 1983;Marshall, 1984;Chiang et al, 1985). This may be the case since rat embryo fibroblasts that have been experimentally immortalized by transfection with a c-myc-containing plasmid acquire the ability to grow in soft agar in response to only EGF (Stern et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…After 12 h, cells were washed twice with phosphate-buffered saline and cultured in either serum-free medium or serum-free medium supplemented with 50 ng of selenous acid per ml (26). Serum-free medium consisted of a 1:1 (vol/vol) mixture of Ham's F-12 (Life Technologies) and DMEM plus 25 g of bovine holo-transferrin per ml, 10 g of bovine insulin per ml, 10 ng of mouse epidermal growth factor per ml, and 25 g of human high-density lipoprotein per ml (17). Cells were harvested after another 48 h.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…In initial attempts to formulate a serum-free medium for salmon embryo cells analogous to previous work with rodent embryo cells (26,27), we were unsuccessful in formulating a combination ofmedium supplements from known hormones, attachment proteins, binding proteins, and nutritional factors that would allow sustained growth of CHSE-214 chinook salmon embryo cells. These results led us to explore other potential sources of mitogenic activity for salmonid cells in vitro.…”
Section: Resultsmentioning
confidence: 99%